IPS Empress onlays luted with two dual-cured resin cements for endodontically treated teeth: a 3-year clinical evaluation - (:unkn) unknown (My University, 2011)
The aim of this study was to evaluate the performance of IPS Empress ceramic onlays luted with two dual-cured adhesive resin cements for endodontically treated teeth. Twenty molar teeth were restored with all-ceramic restorations luted randomly with Maxcem or Clearfil Esthetic Cement and DC Bond Kit luting systems (n = 10 each) in 20 patients. The restorations were assessed using modified US Public Health Service criteria at baseline, 6 months, and 1, 2, and 3 years. A statistically significant deterioration was found for the criteria marginal integrity, anatomical form, and surface roughness. For luting of ceramic onlays, no difference between the two luting systems was detected.
Keywords: Humans; Follow-Up Studies; Root Canal Therapy; Dental Porcelain; Surface Properties; Molar; Aluminum Silicates; Resin Cements; Tooth Preparation; Dental Marginal Adaptation; Inlays; Color; Photography, Dental; Radiography, Bitewing; Tooth, Nonvital